"CHEMICAL ROULETTE": GAMIFICATION IN TEACHING THE NOMENCLATURE OF COMPLEX COMPOUNDS (REMUNOM, 2025)
The complexity of the IUPAC rules for naming complex compounds makes this content one of the most challenging in analytical chemistry teaching. To overcome this difficulty, the “Chemistry Roulette” educational game was developed as na interactive alternative to revise and fix concepts considered abstract by students. The material was produced by hand from recyclable and low-cost resources, incorporating a themed roulette wheel, question cards and na answer card that guides the correction. The dynamic is based on successive draws that determine the challenges to be answered, encouraging quick decision-making and the practical application of knowledge. The game was applied in na academic environment and evaluated using na evaluation form. It was positively accepted by the students, who highlighted its attractiveness, clarity and contribution to learning. The results show that Chemistry Roulette is na innovative teaching strategy, capable of transforming learning into a more participatory, motivating and effective process.